Developing technological capability through human resource management: case study from the Philippines. Issue 2 (4th May 2017) - Del Prado, Fatima Lourdes E.; Rosellon, Maureen Ane D.
ABSTRACT: This paper examines firms' human resource management strategies for innovation and technological upgrading. Using the information collected from three manufacturing firms in the Philippines, this paper describes how human resource (HR) management practices stimulate innovation processes and contribute to technological capabilities of firms. The findings reveal that HR practices, in particular recruitment, and training and development functions influence skills and capacity upgrading to some extent. For firms to sustain and step up their technological capabilities, a more formal and systematic innovation and technological upgrading strategy must be pursued.